Respuesta :

timo86

Answer:

[tex]\sqrt[5]{4}[/tex]  + [tex]\sqrt[10]{3}[/tex]

Step-by-step explanation:

We sure can write 2^2/5+ 3^1/10 as [tex]2^{\frac{2}{5} } + 3^{\frac{1}{10} }[/tex]

// use the [tex]a^{\frac{m}{n} } =\sqrt[n]{a^{m} }[/tex] to transform the expression

Convert [tex]2^{\frac{2}{5} }[/tex] to [tex]\sqrt[5]{2^{2} }[/tex] = [tex]\sqrt[5]{4}[/tex]                        (here a = 2, n = 5, m = 2)

Then convert  [tex]3^{\frac{1}{10} }[/tex] to [tex]\sqrt[10]{3^{1} }[/tex] = [tex]\sqrt[10]{3}[/tex]             (here a = 3, n = 10, m = 1)

Now we get  [tex]2^{\frac{2}{5} } + 3^{\frac{1}{10} }[/tex] = [tex]\sqrt[5]{4}[/tex]  + [tex]\sqrt[10]{3}[/tex] . This is the simplified form, which is the answer.